A Fresh Look at Boso&r: Textual Criticism in 2 Peter 2:15 - Hays, Christopher M. (Filología neotestamentaria, 2004)
Commentators have often been stymied by the idiosyncratic patronymic Boso&r assigned to Balaam of Beor by the best textual witnesses of 2 Peter 2:15. However, detailed investigation of the development of the Balaam traditions in tandem with the Edomite king-lists of Gen 36:32, 1 Chr 1:43, and Job 42:17d (LXX only) reveals a tightly intertwined history that paved the way for the unintentional replacement of Bew&r with Boso&r. The confusion of numerous other names and places associated with the two titles in the Septuagint and Targums witnesses to a trajectory which culminated in the textual variants of 2 Peter 2.15.